Setting up a serious game for major incident in industrial plants management: investigation of the learning effect. (2018) - Ferretti, Ivan; Mazzoldi, Laura; Zanoni, Simone; Zavanella, Lucio
In recent years the introduction of virtual simulation allowed to improve the management of major incidents by developing tools (or serious games) able to increase awareness of coordination and decision-making abilities in emergency situations. This study presents the results of a new serious game that simulates activities, procedures and processes planned to be implemented to manage the aid during a major incident that may occur in industrial plants. In particular, the serious game presented is based on a discrete event simulator and it is able to reproduce emergency situations in which the players can improve their own management abilities through repetitive random sessions. A detailed analysis of the learning effect over different scenario settings has been investigated through the initial application of the tool to differently experienced set of users. The results presented in this contribution show how the use of the simulator may significantly improve the awareness of coordination and decision-making abilities in emergency situations.